The Role of Urban Spaces in Improving the Life Quality (A Case Study of Malayer) - Robabeh Rajabi Amirabad; Bijan Rahmani (تحقیقات کاربردی علوم جغرافیایی)
The rapid growth of urbanization in recent decades and the neglect of qualitative aspects of human life have had adverse effects on the individual and social health of the community and urban life. Generally, life quality addresses social, environmental, and the economic issues. Plans should be consistent with improving life quality. On the other hand, improving the life quality can result in developments in social, economic, physical and service-providing areas. In this regard, the purpose of this study was to investigate the role of Malayer urban spaces in improving the citizen’s life quality including variables such as the quality of facilities in the city, social environmental, economic quality and environmental quality, , security and relaxation, and so on. The method used in this study was a combination of analytical and case-oriented methods. The type of the study was a developmental one and the area understudy was Malayer with 52697 households and an area of ​​2,400 hectares. Quantitative models and statistical procedures such as development indicators, standardized scores, correlation coefficient, t-test, multiple regression, variance analysis, coefficient of variation, factor analysis, and 60 variables as the indicators of this study were used to assess and evaluate the life quality in Malayer as far as social, economic, environmental and physical aspects of life were concerned. Using Cochran's formula, 384 random samples were selected from different parts of the city and were analyzed through descriptive and inferential statistical analysis using SPSS software. The obtained findings showed that the economic index of life quality with 58% was more inappropriate than the social, cultural and physical ones, while social and cultural indicators with 42% were in a moderate situation. The results also showed that the components of the quality of economic environment, working environment, transportation and the community are in an unfavorable condition in Malayer. Thus it is possible to increase the life quality in Malayer through  improving the economic, social, cultural and relative access to urban services.